Arising motivation in teaching foreign languages.: Arising motivation in teaching foreign languages. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: There are different motifs for people to learn foreign languages: some people learn a foreign language for practical reasons whereas others are enthusiastic for a particular language and the speakers of that language. Those who are learning the language or have already learnt are aware of the career benefits that the language proficiency offer yet some learners need to realize the reason for language learning which can be a motif for them to go further. Motivation and management of their learning behavior are important in effective learning. To push the students to be effective learners and willingly work on themselves they should set goals and visualize the last outcome which is expected to achieve after being proficient in the language they are learning. If a teacher has a strong methodology and arises motivation in the students teaching and learning will be an enjoyable activity. The preliminary duty of the teacher is to encourage the students to set certain goals in front of them at the early stage of their learning process. Because the students do not learn a subject with only their brain but there are other factors too. Motivation factor makes the learners more receptive to new information. However, students do not learn in the same way, some of them learn by listening, some by writing and some other by involving speaking. In order to keep students interested in learning, students must be motivated by the teacher.